Peripheral osteoma of the mandible: case report and review of the literature - Sharma, Mohit (Journal of Kathmandu Medical College, 2017)
Osteomas are benign, slow-growing osteogenic tumors commonly occurring in the craniofacial bones. Osteomas are characterized by the proliferation of compact and/or cancellous bone. It can be of a central, peripheral, or extraskeletal type. The peripheral type arises from the periosteum and is rarely seen in the mandible, if involved, the lingual surface and lower border of the body are the most common locations of these lesions. They are usually asymptomatic and can be discovered in routine clinical and radiographic examination. This paper presents a large solitary peripheral osteoma located in the lingual surface of the right posterior mandible. The osteoma was removed surgically, and no recurrence has been observed. Journal of Kathmandu Medical College, Vol. 5, No. 4, Issue 18, Oct.-Dec., 2016, page: 128-130